2017
DOI: 10.20965/jdr.2017.p0526
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Aperture Radar Interferometry for Disaster Monitoring of Harbor Facilities

Abstract: In this paper, we present experimental results of the disaster monitoring of harbor facilities using spaceborne synthetic aperture radar interferometry (InSAR). The Advanced Land Observing Satellite-2 (ALOS-2 or DAICHI-2), operated by the Japan Aerospace Exploration Agency (JAXA), carries the Phased Array type L-band Synthetic Aperture Radar-2 (PALSAR-2). PALSAR-2 can observe disaster areas day and night, in any weather, at a resolution of approximately 3 m. ALOS-2 PALSAR-2 has been used to measure large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We can measure the absolute deformation by unwrapping the phase as long as the deformation satisfies the sampling theorem. The robustness of DInSAR analysis for harbor facilities is discussed in [20]. In [20], it is reported that the average error of the 11 observations was 0.1 cm, and its standard deviation was 0.4 cm for ideal case.…”
Section: Differential Interferometric Sarmentioning
confidence: 99%
See 3 more Smart Citations
“…We can measure the absolute deformation by unwrapping the phase as long as the deformation satisfies the sampling theorem. The robustness of DInSAR analysis for harbor facilities is discussed in [20]. In [20], it is reported that the average error of the 11 observations was 0.1 cm, and its standard deviation was 0.4 cm for ideal case.…”
Section: Differential Interferometric Sarmentioning
confidence: 99%
“…The robustness of DInSAR analysis for harbor facilities is discussed in [20]. In [20], it is reported that the average error of the 11 observations was 0.1 cm, and its standard deviation was 0.4 cm for ideal case. That is, there was no systematic error of more than 0.1 cm when we apply the averaging filter when it contains a 0.4 cm variation inside the averaging window.…”
Section: Differential Interferometric Sarmentioning
confidence: 99%
See 2 more Smart Citations
“…This result, for example, suggests that the sensitivity of the temporal coherence decrease should be clarified in terms of the damage level and/or building size. If we could find the sensitivity and the limitation of the interferometric coherence analysis, we could perform a damage assessment for every building and facility [26].…”
Section: Introductionmentioning
confidence: 99%